Pulpectomy of acute periapical periodontitis performed in a single appointment in an infant patient. Case report - Palomino Ríos, Ethel Violeta (2022)
The use of medicated pastes in the treatment of dental abscesses through the pulpectomy procedure helps to keep the primary teeth affected. The objective of this treatment was to evaluate the clinical and radiographic success of the modification of the intracanal obturation mechanism of the pulpectomy performed in a single appointment. The clinical case report in a 2-year-10-month-old male with a diagnosis of acute apical periodontitis is presented, where a pulpectomy was performed in a single appointment. In the clinical evaluation at 7 days, clinical silence and absence of dental abscess were observed. At one month and at 4 months there was also absence of dental abscess and symptoms. At 12 months, in a new clinical evaluation, clinical silence was maintained and radiographically an absence of radiolucent pathological interradicular or periapical image was observed and bone regeneration was evidenced. One-appointment pulpectomy can be considered an effective treatment for maintaining the integrity of the affected primary tooth, but more studies and long-term follow-ups are required to evaluate this obturation modification used in this type of pulpectomy.